2016
DOI: 10.5194/gmd-2016-71
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Vulnerability, Impacts, Adaptation, and Climate Services (VIACS) Advisory Board for CMIP6

Abstract: Abstract. The Vulnerability, Impacts, Adaptation, and Climate Services (VIACS) Advisory Board was created to provide a strong bridge between climate change applications experts and climate modelers for the Sixth Phase of the Coupled Model Intercomparison Project (CMIP6). The climate change application community comprises researchers and other specialists who make use of climate information (alongside other socioeconomic and environmental information) to analyze vulnerability, impacts and adaptation of natural … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…In particular, for larger LULCC areas, there were statistically significant changes in albedo and partitioning between latent and sensible fluxes, which would contribute to the significant changes in surface air temperature found. For these reasons, the agricultural community requested that temperature and moisture variables from the agricultural fraction of grid boxes be included as output to capture the differential impact of climate change on agricultural lands [Ruane et al, 2016]. The authors also found that the LULCC became more important as a forcing under the RCP2.6 scenario [Brovkin et al, 2013], as the radiative forcing due to GHG emissions stabilize.…”
Section: Including Agricultural Nitrogen Fertilizer Applicationsmentioning
confidence: 99%
“…In particular, for larger LULCC areas, there were statistically significant changes in albedo and partitioning between latent and sensible fluxes, which would contribute to the significant changes in surface air temperature found. For these reasons, the agricultural community requested that temperature and moisture variables from the agricultural fraction of grid boxes be included as output to capture the differential impact of climate change on agricultural lands [Ruane et al, 2016]. The authors also found that the LULCC became more important as a forcing under the RCP2.6 scenario [Brovkin et al, 2013], as the radiative forcing due to GHG emissions stabilize.…”
Section: Including Agricultural Nitrogen Fertilizer Applicationsmentioning
confidence: 99%
“…The observable variation in the seasonal cycle of the snow albedo is then a useful proxy for constraining the unobservable feedback strength to climate warming, as both are driven by the same physical mechanisms on different timescales. Other examples include constraints on climate-carbon feedbacks (Cox et al, 2013;Wenzel et al, 2014), the Austral jet stream position (Wenzel et al, 2016), cloud feedbacks and equilibrium climate sensitivity (Huber et al, 2011;Fasullo and Trenberth, 2012;Fasullo et al, 2015;Klein and Hall, 2015;Knutti et al, 2006;Sherwood et al, 2014), and relations of past and future sea ice or temperature trends (Boé et al, 2009;Knutti and Tomassini, 2008;Mahlstein and Knutti, 2012;Massonet et al, 2012). The ScenarioMIP design will allow for testing emergent constraint results under various forcing pathways.…”
Section: Scientific Questions Addressed By Scenariomipmentioning
confidence: 99%